Participatory-Transcendental Education: A Qualitative Study on the Collaboration-Convergence of Paulo Freire's Liberating education and Islamic Education - Umiarso Umiarso; Dina Mardiana (AT-TURATS, 2022)
This research focused on the collaboration-convergence construction of Freire’s liberating education and Islamic education systems. These two systems are integrated into a single dimension of education that has spiritual roots. Therefore, this research tries to analyze Paulo Freire’s educational thinking, which is elaborated, collaborated, converged, and integrated with Islamic education’s theological and philisophical values. This research approach uses a qualitative type of literature study, so it tended to use documentation techniques in collecting its data. The data in this research were analyzed using the interactive analysis of Miles, Hubermann and Saldana. With this method, this research can be more detailed and comprehensive to understand and interpret Freire’s liberation education thinking and Islamic education. This research finds that Freire's education system has an axiological basis of secular humanism that can be collaborated and converged with the values of transcendental humanism in Islamic education. From this collaboration-convergence process, an education system has been created. It has an ontological basis and is integrated with theological values. It is also an axiological dimension of trancendental humanism. This education system has a mission to realize transcendental humanism in the educational process so that this system can be referred to as participatory-trancendental education.